A neural mechanism of the relationship between impulsivity and emotion dysregulation in patients with Internet gaming disorder. (4th May 2020) - Shin, Yu‐Bin; Kim, Hyunji; Kim, Soo‐Jeong; Kim, Jae‐Jin
Abstract: Impulsivity and emotion dysregulation have been known to be risk factors for Internet gaming disorder (IGD), but their underlying neural mechanisms are not yet fully understood. Given that the prefrontal cortex has a key role in higher order cognition and addiction, the present study aimed to investigate emotional influences on response inhibition in situations with different cognitive demands. A total of 41 young male adults (20 with and 21 without IGD) were scanned while performing two versions of an emotional go/no‐go task with demands on low and high working memory load. Patients with IGD showed a failure in response inhibition and increased activation of widespread brain regions, including prefrontal, motor‐sensory, parietal, occipital, insula, and striatal regions across tasks. Among these regions, involvement of the dorsolateral prefrontal cortex and ventral striatum was observed only during the task with high demands on working memory. Moreover, it was also only during the high‐load task that interaction between response inhibition and emotional states was observed in the dorsomedial prefrontal cortex, with observations revealing that its alteration in patients with IGD was associated with number of hours spent on Internet gaming. Our findings highlight a failure of response inhibition and dysfunction within the inhibitory control network. The special significance of our study is that dysfunctional dorsomedial prefrontal cortex may mediate abnormal emotional influences on response inhibition in patients with IGD. Abstract : It was only during the high‐load task that interaction between response inhibition and emotional states was observed in the dorsomedial prefrontal cortex, with observations revealing that its alteration in patients with IGD was associated with number of hours spent on Internet gaming. Dysfunctional dorsomedial prefrontal cortex may mediate abnormal emotional influences on response inhibition in patients with IGD.